A Comparative Study of the Fertilizer-Cum-Pesticide Effect of Vermicomposts Derived from Cowdung and the Toxic Weed Lantana - Naseer Hussain; Tabassum-Abbasi; Tasneem Abbasi; Shahid Abbas Abbasi (Agriculture, 2021)
The effect of vermicomposts, derived either from cowdung or the pernicious invasive plant lantana (Lantana camara), has been assessed on the seed germination, plant growth, fruit yield, quality of the produce, and disease resistance of a common vegetable, ladies finger (Abelmoschus esculentus).Seeds of A. esculentus were germinated and grown in soil fertilized with 0, 2.5, 3.75 and 5 t ha−1 of lantana or cowdung vermicompost for 4 months. It was seen that the lantana vermicompost performed at par or better than the cowdung vermicompost in terms of most of the growth and yield parameters observed. Both the vermicomposts encouraged the germination, growth as well as the yield of ladies fingers. The fruits harvested from the vermicompost-treated plots had greater concentrations of minerals, proteins and carbohydrates than the control plants. Vermicomposts also reduced the incidence of pest attacks on the plants. The results confirm that vermicomposting destroys the harmful ingredients of lantana and turns it into as good a biofertilizer, perhaps even better than the vermicompost of cow-dung. The very large quantities of lantana biomass that is generated in the tropical and sub-tropical regions of the world every year, which presently go to waste, now appear capable of becoming a source of organic fertilizer.